2000
DOI: 10.1542/peds.106.2.e18
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Colonization of Toys in Neonatal Intensive Care Cots

Abstract: ABSTRACT. Objectives. To investigate the bacteria and fungi contaminating toys in neonatal intensive care unit (NICU) cots, the colonization rates, and factors that influence them.Methods. A cross-sectional, longitudinal bacteriologic survey of all toys in the cots of infants in an NICU. All the toys in an infant's cot were cultured weekly for 4 weeks. Data were collected on the infant's postnatal age, the type of cot, whether humidity was added, characteristics of the toy, and any infant infections.Results Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 9 publications
0
37
0
1
Order By: Relevance
“…While the level and extent of streptococcal fomite contamination have not been well explored in the literature, the few existing studies provide an alarming perspective. Direct bacteriologic cultures have found that between 4% and 11% of toys are often positive for streptococci (31)(32)(33), and culture-independent methods have identified a high abundance of streptococcus-related species in toddler day care rooms (34). In this study, we found that both S. pneumoniae and S. pyogenes could be cultured from soft toys found in a day care center.…”
Section: Discussionmentioning
confidence: 65%
“…While the level and extent of streptococcal fomite contamination have not been well explored in the literature, the few existing studies provide an alarming perspective. Direct bacteriologic cultures have found that between 4% and 11% of toys are often positive for streptococci (31)(32)(33), and culture-independent methods have identified a high abundance of streptococcus-related species in toddler day care rooms (34). In this study, we found that both S. pneumoniae and S. pyogenes could be cultured from soft toys found in a day care center.…”
Section: Discussionmentioning
confidence: 65%
“…Six studies made inconclusive or poorly reported attempts at linking the strains between patients and the equipment/environment 27–30,37,38 . The final four studies did not relate the MRSA strains found on the equipment/environment to that found in the patients within the setting 24,31,39,40 …”
Section: Resultsmentioning
confidence: 99%
“…Toys may be considered as part of the equipment of a paediatrician's office, but sharing of toys poses a potential health risk. Microbial contamination of toys has been documented in hospitals, physician's offices and day care centres (43)(44)(45). Fecal coliforms and rotavirus have been found on toys in day care centres and in hospital (46,47).…”
Section: Toys and Transmission Of Infectionmentioning
confidence: 99%